CORPORATE SOCIAL RESPONSIBILITY UNTUK MENINGKATKAN NILAI PERUSAHAAN - Andoko (Jurnal Mahkota Bisnis (Makbis), 2024)
The concepts of Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) have gained significant prominence in recent years. Historically, the primary focus in business management was the company's financial performance. However, with the growing emphasis on mitigating climate change, generating profits for investors is no longer the sole consideration in business management. More investment metrics are now giving attention to environmental protection, social responsibility, corporate governance, and other aspects that promote coexistence and shared prosperity. CSR is a broad concept of sustainability, whereas ESG represents the approach to implementing CSR principles. Therefore, sustainable management is the overarching goal that businesses should aim for. Today, many companies prioritize CSR in shaping their corporate policies. Engaging in CSR activities is undoubtedly beneficial for enhancing a company’s image, but it also has inevitable effects on resource allocation. Therefore, it is important to assess the benefits and costs of CSR activities, particularly their impact on a company's financial performance.